Strengthening Identity Through the Integration of Local History in the Learning Curriculum - Sariyatun, Sariyatun; Marpelina, Leni (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
In Indonesia, with its rich cultural diversity, strengthening identity is increasingly important for both individuals and communities. The integration of local history into learning curriculums is one method to achieve this strengthening of identity. This research aims to examine how the integration of local history can reinforce identity. The study employs a literature review approach, gathering data and information from various sources, including books, articles, and journals. The collected data encompasses theories on identity, previous research on local history integration, and practices of local history integration. The findings indicate that integrating local history strengthens identity in three ways: (1) developing a sense of belonging and connection with the community, (2) enhancing understanding of cultural roots, and (3) developing critical thinking skills and problem-solving abilities. The research concludes that the integration of local history is an effective strategy for strengthening identity.